2022
DOI: 10.3389/fonc.2022.796391
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic and Grading Accuracy of 68Ga-DOTATATE and 18F-FDG PET/MR for Pancreatic Neuroendocrine Neoplasms

Abstract: Accurate diagnosis and grading are critical for pancreatic neuroendocrine neoplasm (pNEN) management. This study compares the diagnostic and grading value of 68Ga-DOTATATE PET/MR and 18F-FDG PET/MR for pNENs separately as well as in combination. A total of 36 patients with histologically confirmed pNENs, who underwent both 68Ga-DOTATATE PET/MR and 18F-FDG PET/MR within 2 weeks from 2020 to 2021, were retrospectively collected and analyzed. The maximum standardized uptake values of 68Ga-DOTATATE (G-SUVmax) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…68 Ga-DOTA-SSA PET/CT is also important for determining radionuclide uptake, which is associated with the response to peptide receptor radionuclide therapy (PRRT) ( 20 ). Research has found that 68 Ga-DOTA-SSA PET/CT can effectively discriminate between low-grade and high-grade pNENs but cannot further differentiate G3 pNETs and pNECs ( 21 ). Due to outstanding diagnostic sensitivity of the 18 F-FDG PET/CT for G3 pNET and pNEC, it is frequently employed in clinical practice in conjunction with 68Ga-DOTA-SSA PET/CT to increase disease diagnostic sensitivity and precise staging ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…68 Ga-DOTA-SSA PET/CT is also important for determining radionuclide uptake, which is associated with the response to peptide receptor radionuclide therapy (PRRT) ( 20 ). Research has found that 68 Ga-DOTA-SSA PET/CT can effectively discriminate between low-grade and high-grade pNENs but cannot further differentiate G3 pNETs and pNECs ( 21 ). Due to outstanding diagnostic sensitivity of the 18 F-FDG PET/CT for G3 pNET and pNEC, it is frequently employed in clinical practice in conjunction with 68Ga-DOTA-SSA PET/CT to increase disease diagnostic sensitivity and precise staging ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SSTR-PET/MRI incorporating hepatobiliary phase imaging is a useful modality in patients with liver dominant NET. However, there is only very little data in NET and PET/MRI available [128,[139][140][141][142][143].…”
Section: Neuroendocrine Tumorsmentioning
confidence: 99%
“…( Figure 2 ) This allows the use of PET/CT imaging to detect SSTR-expressing PNET with sensitivity of 93% and specificity of 91% [ 24 ]. 68Ga-DOTATATE PET/CT has demonstrated efficacy in the detection of primarily low-grade tumors, G1 and G2 PNETs, with detection rates that have been reported as 95% and 87.5%, respectively [ 25 ]. However, for higher grade tumors (G3), this imaging modality is significantly less effective, with 37.5% detected [ 25 ].…”
Section: Presentation and Diagnosis Of Pancreatic Neuroendocrine Tumorsmentioning
confidence: 99%
“…68Ga-DOTATATE PET/CT has demonstrated efficacy in the detection of primarily low-grade tumors, G1 and G2 PNETs, with detection rates that have been reported as 95% and 87.5%, respectively [ 25 ]. However, for higher grade tumors (G3), this imaging modality is significantly less effective, with 37.5% detected [ 25 ]. An additional work-up should be pursued in patients with high clinical suspicion and negative DOTATATE scan, such as traditional radiolabeled fluorodeoxyglucose (FDG) PET imaging.…”
Section: Presentation and Diagnosis Of Pancreatic Neuroendocrine Tumorsmentioning
confidence: 99%